A framework for physiological indicators of flow in VR games: construction and preliminary evaluation. Issue 5 (October 2016) - Bian, Yulong; Yang, Chenglei; Gao, Fengqiang; Li, Huiyu; Zhou, Shisheng; Li, Hanchao; Sun, Xiaowen; Meng, Xiangxu
Abstract Flow experience is often considered as an important standard of ideal user experience (UX). Till now, flow is mainly measured via self-report questionnaires, which cannot evaluate flow immediately and objectively. In this paper, we constructed a physiological evaluation model to evaluate flow in virtual reality (VR) game. The evaluation model consists of five first-level indicators and their respective second-level indicators. Then, we conducted an empirical experiment to test the effectiveness of partial indicators to predict flow experience. Most results supported the model and revealed that heart rate, interbeat interval, heart rate variability (HRV), low-frequency HRV (LF-HRV), high-frequency HRV (HF-HRV), and respiratory rate are all effective indicators in predicting flow experience. Further research should be conducted to improve the evaluation model and conclude practical implications in UX and VR game design.